Increasing Student Learning Interest through Coopreative Learning and Interactive Quiz - Ulfa, Rafika Fauzia; Samsudin, Achmad; Supriatna, Asep; Tresnasih, Eka; Winarno, Nanang (Journal of Disruptive Learning Innovation (JODLI), 2024)
Cooperative learning is one of the learning strategies that is implemented collaboratively or cooperatively among students. With good cooperation, it is expected that there will be high communication, interest and motivation in learning. Cooperative learning needs to be integrated with assessments in the form of interactive quizzes so that students are more interested in participating in learning. The purpose of this study was to determine the effect of cooperative learning with interactive quizzes conducted through Classroom Action Research (CAR). From the results of the study, it was found that the pretest and posttest of excretory system material in the first and second cycles experienced a significant increase. While between the first cycle and the second cycle did not experience a significant increase. Analysis of student interest in learning in each cycle and between cycles did not experience a significant increase. The results of the study were then analyzed descriptively with the support of supporting articles.